2010
DOI: 10.2478/v10190-010-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Antarctic Tundra Ecosystem to Climate Change and Human Activity

Abstract: ABSTRACT:Over the last couple of years the Antarctic Peninsula region has been one of the fastest warming regions on the Earth. Rapidly proceeding deglaciation uncovers new areas for colonisation and formation of Antarctic tundra communities. The most evident dynamics, i.e. changes in both biodiversity and structure of tundra communities, are observed in the forefi elds of retreating glaciers. This paper presents examples of changes in biodiversity and in the direction and rate of succession changes taking pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The diverse avian and mammalian species and vegetation are the reason why the protected area of ASPA-128 was created. It has been shown that newly ice-free areas are dynamically colonised by plant communities [16] and nesting bird populations. Algae, lichens, mosses, fungi, and plants have colonized these recently formed ice-free areas on the glacier forefields and nunataks [17,18].…”
Section: Characterization Of the Research Areamentioning
confidence: 99%
“…The diverse avian and mammalian species and vegetation are the reason why the protected area of ASPA-128 was created. It has been shown that newly ice-free areas are dynamically colonised by plant communities [16] and nesting bird populations. Algae, lichens, mosses, fungi, and plants have colonized these recently formed ice-free areas on the glacier forefields and nunataks [17,18].…”
Section: Characterization Of the Research Areamentioning
confidence: 99%
“…Long term studies on dynamics of tundra ecosystem due to climatic changes carried out in the maritime Antarctic (Chwedorzewska 2010), especially in the Antarctic Peninsula region, indicate rapid transformations of the Antarctic tundra communities (Olech 2010). Among others the shrinkage of the glaciers extents or disappearance of communities preferring moist substratum, especially bryophytes, were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the substrate humidity causes overgrowing of mossy communities by the grass Deschampsia antarctica. In this Antarctic region the modifi cations of tundra communities towards grassifi cation are noticed (Olech 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations